2019
DOI: 10.1590/1809-6891v20e-51187
|View full text |Cite
|
Sign up to set email alerts
|

Productive Performance of Pre-Weaned Calves Reared in the Pantanal

Abstract: Early weaning (EW) has been adopted in cattle breeding farms in Pantanal as a strategy to increase the rate of pregnancy in cows. The primary income of these properties is the production of beef calves, and the price of these animals depends on their weight. Therefore, the calves subjected to EW should present weight similar to or higher than those of calves subjected to conventional weaning (CW). This study aimed to evaluate the productive performance of pure (Nellore) calves and crossbred (Nellore/Angus) cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Early weaning emerges as a promising strategy to optimize the metabolic status of cows, playing a crucial role in improving conception rates during the subsequent reproductive season [ 21 , 22 ]. A parallel study conducted by our research group involving 208 lactating cows (including those from the present study) revealed that cows subjected to early weaning showed an approximately 28% greater pregnancy rate in two fixed-time artificial inseminations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early weaning emerges as a promising strategy to optimize the metabolic status of cows, playing a crucial role in improving conception rates during the subsequent reproductive season [ 21 , 22 ]. A parallel study conducted by our research group involving 208 lactating cows (including those from the present study) revealed that cows subjected to early weaning showed an approximately 28% greater pregnancy rate in two fixed-time artificial inseminations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although early weaning is an interesting strategy to enhance the reproductive performance of cows, this practice can entail significant disadvantages for calves, mainly when adequate nutritional conditions are not provided after this period [ 25 ]. Studies on early weaning in beef calves have revealed that the implementation of post-weaning supplementation strategies can equalize the performance of traditionally weaned calves, especially when the latter do not receive supplementation [ 16 , 21 , 27 ]. In the present study, the results indicate that calves in the EW group exhibited reduced body weight compared with those in the CW group from 240 days of age and continuing throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%